Pengembangan LKPD Berbasis Model Kooperatif Think Pair-Share Untuk Meningkatkan Aktivitas Belajar - Fitriani Nur; Andi Fajrin Syarif; Sitti Mania; Suharti Suharti (JP3M (Jurnal Penelitian Pendidikan dan Pengajaran Matematika), 2021)
The purpose of this research is to make LKPD based on TPS cooperative model in order to increase student mathematics learning activities. This study applies the plomp development model with data collection techniques in the form of observation guides, questionnaires, and tests. The subjects are students in class IX from MAN 1 Makassar. From the development activities, the results stated that was made could increase the learning activities of students which were strengthened by the fulfillment of 5 points from 6 predetermined ideal criteria, and the fulfillment of points 3-6 which were the essence of learning. This LKPD has also fulfilled the validity, practicality, and effectiveness of a product made, namely the acquisition of the validity category is very valid, the practicality category is positive, and the effectiveness category is very positive.